2023
DOI: 10.3389/ti.2023.10800
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Blockchain Technology Could Increase Equity and Transparency in Organ Transplantation: A Narrative Review of an Emergent Tool

Abstract: In the last few years, innovative technology and health care digitalization played a major role in all medical fields and a great effort worldwide to manage this large amount of data, in terms of security and digital privacy has been made by different national health systems. Blockchain technology, a peer-to-peer distributed database without centralized authority, initially applied to Bitcoin protocol, soon gained popularity, thanks to its distributed immutable nature in several non-medical fields. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The blockchain adds a new layer to the Internet to enable financial transactions, including immediate advanced cash installments (in a widely usable digital currency) and longer-term, increasingly complex budgetary contracts. Blockchains can execute financial contracts, currencies, and soft or hard resources [28]. The blockchain can also track, observe, and execute transactions.…”
Section: Figure 2 the Working Algorithm Of Blockchainmentioning
confidence: 99%
“…The blockchain adds a new layer to the Internet to enable financial transactions, including immediate advanced cash installments (in a widely usable digital currency) and longer-term, increasingly complex budgetary contracts. Blockchains can execute financial contracts, currencies, and soft or hard resources [28]. The blockchain can also track, observe, and execute transactions.…”
Section: Figure 2 the Working Algorithm Of Blockchainmentioning
confidence: 99%
“…On the other hand, the challenge of the blockchain-based OTP system is primarily related to its difficulties in transforming the centralised approach to information management into a decentralised structure while maintaining the security and privacy of sensitive and personal data. Upon closer inspection, it became evident that the surveys and systematic reviews [15][16][17][18] that have been carried out up to this point have focused more on the conceptual frameworks than the technical components of the articles they have included. From a technical standpoint, it was found that they frequently considered the chain type and blockchain platform.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [15] has examined the six studies on blockchain-based organ transplantation in terms of the blockchain platform used and the contributions they provided. Accordingly, it was stated that in addition to the potential benefit of blockchain, there is a need to conduct research on data management systems that can work together with these systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations